How Can Access to Mental Health Services in Switzerland Be Improved in the Aftermath of the COVID-19 Pandemic? - Camilla Sculco; Marco Meneguzzo; Emiliano Albanese (Public Health Reviews, 2025)
BackgroundThe global spread of the COVID-19 pandemic posed exceptional challenges for society and healthcare systems, with adverse effects on population’s mental health. Understanding the pandemic’s impact on mental health and service use in Switzerland is a priority, along with outlining evidence-based recommendations to improve access and support for those in need.AnalysisStudies from Switzerland report a growing burden of psychological distress, especially among vulnerable groups such as children, adolescents, young women, socially isolated individuals, and those with pre-existing health conditions. The pandemic also caused variations in mental health service use across the country.Policy Options[1] Strengthening mental health services for vulnerable populations. [2] Re-structuring mental health services and their capacity to cope with the increasing demand. [3] Enhancing prevention and promotion of mental health and wellbeing.ConclusionIn the aftermath of the pandemic, there is a need to strengthen and restructure mental health services, enhance prevention and promotion efforts, and integrate mental health into pandemic preparedness to mitigate the long-term impacts of future public health emergencies.